2018
DOI: 10.2337/db18-1903-p
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Perilipin 2 Induces Cardiac Steatosis and Atrial Fibrillation via Connexin 43 Remodeling

Abstract: Atrial fibrillation (AF) is prevalent among diabetic patients. Diabetes is also associated with myocardial lipid droplet accumulation (steatosis), which is thought to be a source of intracellular lipotoxicity. Since the relative contribution of cardiac steatosis per se to AF has not been elucidated, the current study was designed to clarify the causal effect of cardiac steatosis on AF using an aged mouse model of cardiac steatosis. Cardiac-specific perilipin (PLIN) 2-overexpressing mice (PLIN2-Tg) were created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Using their own method, Fukui and others demonstrated that hyperleptinemia increased AF susceptibility in mice maintained on a high-fat diet (Fukui et al, 2017). Another study reported that perilipin 2 (Plin2) overexpression increased sustained AF in mice due to atrial steatosis (Sato et al, 2019). While these authors defined sustained AF as an episode lasting longer than 5 min, other definitions have been more commonly used, including 10 s (Aschar-Sobbi et al, 2015), 15 s (Bruegmann et al, 2018), and 30 s (Jansen et al, 2017;Jansen et al, 2019).…”
Section: Examples Of Usementioning
confidence: 99%
“…Using their own method, Fukui and others demonstrated that hyperleptinemia increased AF susceptibility in mice maintained on a high-fat diet (Fukui et al, 2017). Another study reported that perilipin 2 (Plin2) overexpression increased sustained AF in mice due to atrial steatosis (Sato et al, 2019). While these authors defined sustained AF as an episode lasting longer than 5 min, other definitions have been more commonly used, including 10 s (Aschar-Sobbi et al, 2015), 15 s (Bruegmann et al, 2018), and 30 s (Jansen et al, 2017;Jansen et al, 2019).…”
Section: Examples Of Usementioning
confidence: 99%